2002
DOI: 10.1046/j.1532-5415.2002.50016.x
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus in a Subgroup of Older Mexicans: Prevalence, Association with Cardiovascular Risk Factors, Functional and Cognitive Impairment, and Mortality

Abstract: These studies highlight some important similarities and differences in comparing a middle class subgroup of older diabetics in Mexico City with diabetics of Mexican origin living in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 46 publications
1
31
2
Order By: Relevance
“…Women with a longer duration of diabetes experienced more decline. Other longitudinal studies have also demonstrated greater cognitive decline in diabetics [36,37], with one Mexican study finding no relationship [38].…”
Section: Discussionmentioning
confidence: 99%
“…Women with a longer duration of diabetes experienced more decline. Other longitudinal studies have also demonstrated greater cognitive decline in diabetics [36,37], with one Mexican study finding no relationship [38].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have found that persons with diabetes mellitus have greater functional decline than other older persons [59][60][61][62][63][64]. Persons with diabetes are much less likely to read, garden, use the telephone, write letters or go out socially [65].…”
Section: Diabetes Mellitusmentioning
confidence: 97%
“…It poses a significant health burden on the basis of increases in morbidity, mortality, and cost, a fact that has been proven repeatedly [31]. In addition, diabetes mellitus is associated with functional impairment in the aging male [32,33,34]. The objective of the Third National Health and Nutrition Examination Survey 1988-1994 (NHANES III), to examine the prevalence and time trends for diagnosed and undiagnosed diabetes according to age, sex, race or ethnic groups in the US population, showed that the prevalence significantly increases with age, in addition to being higher among certain racial minority populations.…”
Section: Why Is Metabolic Syndrome In the Geriatric Population Importmentioning
confidence: 99%